Kerjasama Bagi Hasil Akad Muzara’ah Kritik Putusan Pengadilan Agama Banyuwangi Nomor 3252/Pdt.g.2016/Pa.Bwi - Anam, Mohamad Hoirul (Momentum : Jurnal Sosial dan Keagamaan, 2018)
Abstrac: The agreement for profit sharing cooperation should be recorded in accordance with the applicable law so that it is mutually binding and does not result in fraud from either party either the violation or the betrayal of the cooperation agreement. This can be seen in Case Number 3252 / Pdt.G / 2016 / PA.Bwi. concerning cancellation of the muzara'ah contract. This research is a descriptive legal research, data collection is done by examining the lawsuit file, peace and the decision of the Panel of Judges. The results of this study, 1. The basis of the claim is the background of the denial or betrayal of one of the parties, namely land owners who feel jealous of land managers (cultivators) related to the harvest of dragon fruit. 2. The mediation process carried out based on PERMA No. 1 of 2016 concerning Mediation Procedures and Successfully Achieved an Agreement. 3. Legal products are Determination of case revocation.